ANALISIS KURIKULUM PADA MATA PELAJARAN AKIDAH AKHLAK BERLANDASKAN KEIMANAN DI MADRASAH IBTIDAIYAH - Sabiqa Awwalina, Linlin; Nugraha, Mulyawan Safwandy (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
Formal education institutions have not been able to fully implement an independent curriculum as a simplification of the previous curriculum by strengthening the profile of Pancasila students. The philosophical basis for curriculum formation refers to the thoughts of philosophers in terms of empirical rational analysis based on Islamic theology. The method used in this research is library research or literature study by collecting relevant data and sources, both from book journals and conference results to be used as a reference in analyzing the data. The data analysis technique carried out was to identify themes related to research results and linked to relevant theories, resulting in innovation in designing philosophical and theological foundations in the subject of akidah, morals based on faith. The results obtained show that the philosophical and ontological, psychologycal, socio cultural and technology foundations in developing the Islamic teaching curriculum influence the goals of Islamic education in forming individuals with noble character. The formation of monotheism in the family environment is the main foundation in laying the foundations of faith to be used as capital in facing the environment that students will face in the formal education environment. Teachers are tasked with providing material related to the formation of Islamic values with various strategies or methods used to integrate knowledge with the formation of expected morals.